A model of white supply chain management for sustainable performance in the food industry: A systematic literature review - Waraporn Suksanchananun; Singha Chaveesuk; Wornchanok Chaiyasoonthorn (My University, 2023)
The objective of this study was to create a white supply chain management model that could improve sustainability in the food industry. This model was developed based on a systematic literature review approach. 150 articles written from 2001 to 2021 that were concerned with green supply chain management, corporate social responsibility and ethical concepts were consulted. By analyzing the title, abstract and content of each article thoroughly, and then categorizing the articles, 37 main articles were selected. The researchers further categorized the 37 articles in table form, sorting them and selecting the variables that were used repeatedly. These iterative variables were used to construct a white supply chain management model, and the relationships between the variables were clarified. The researchers were able to produce a model of white supply chain management for sustainable performance in the food industry. However, this model will be validated by structural equation modelling techniques at a later date.
Keywords: Innovation and Socioeconomic Development; Food Waste Reduction and Sustainability; Sustainable Supply Chain Management